2019
DOI: 10.3390/min9050296
|View full text |Cite
|
Sign up to set email alerts
|

The System K2CO3–CaCO3–MgCO3 at 3 GPa: Implications for Carbonatite Melt Compositions in the Shallow Continental Lithosphere

Abstract: Potassic dolomitic melts are believed to be responsible for the metasomatic alteration of the shallow continental lithosphere. However, the temperature stability and range of compositions of these melts are poorly understood. In this regard, we performed experiments on phase relationships in the system K2CO3–CaCO3–MgCO3 at 3 GPa and at 750–1100 °C. At 750 and 800 °C, the system has five intermediate compounds: Dolomite, Ca0.8Mg0.2CO3 Ca-dolomite, K2(Ca≥0.84Mg≤0.16)2(CO3)3, K2(Ca≥0.70Mg≤0.30)(CO3)2 bütschliite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 70 publications
(127 reference statements)
0
10
0
Order By: Relevance
“…In situ X-ray diffraction study revealed that K 2 Mg(CO 3 ) 2 retains its structure to 8 GPa upon compression at the ambient temperature where it transforms into a monoclinic polymorph [50]. However, the present results at 6 GPa and the results at 3 GPa [37] show a miscibility gap on the K 2 Ca(CO 3 ) 2 -K 2 Mg(CO 3 ) 2 join (Figure 7a-c). This suggests that crystal structures of K 2 Mg(CO 3 ) 2 and K 2 Ca(CO 3 ) 2 at 3-6 GPa and 750-1000 • C are different.…”
Section: Mutual Solubility Of K 2 Ca(co 3 ) 2 and K 2 Mg(co 3 )mentioning
confidence: 52%
See 4 more Smart Citations
“…In situ X-ray diffraction study revealed that K 2 Mg(CO 3 ) 2 retains its structure to 8 GPa upon compression at the ambient temperature where it transforms into a monoclinic polymorph [50]. However, the present results at 6 GPa and the results at 3 GPa [37] show a miscibility gap on the K 2 Ca(CO 3 ) 2 -K 2 Mg(CO 3 ) 2 join (Figure 7a-c). This suggests that crystal structures of K 2 Mg(CO 3 ) 2 and K 2 Ca(CO 3 ) 2 at 3-6 GPa and 750-1000 • C are different.…”
Section: Mutual Solubility Of K 2 Ca(co 3 ) 2 and K 2 Mg(co 3 )mentioning
confidence: 52%
“…In contrast to KCM (Figure 8b), which has two eutectics, NCM has a single eutectic, Na 2 Ca 3 -Na 4 Ca-Na 2 Mg, with a composition of 48Na 2 CO 3 •52(Ca 0.75 Mg 0.25 )CO 3 (Figure 8d). As pressure decreases to 3 GPa, the incipient melting of NCM shifts to 850 • C and controlled by the Na 2 Ca + Na 2 + Na 2 Mg assemblage [45], similar to the K 2 Ca-K 2 -K 2 Mg eutectic established in KCM at 3 GPa and 825 • C [37] (Figure 8a,c). The difference is that the KCM eutectic is Mg-rich, 53K 2 CO 3 •47Ca 0.4 Mg 0.6 CO 3 , while the NCM eutectic is Ca-rich with compositions of 52Na 2 CO 3 •48Ca 0.62 Mg 0.38 CO 3 (Figure 8a,c).…”
Section: Comparison With the Na-bearing Systemmentioning
confidence: 67%
See 3 more Smart Citations